Pengaruh Model Pembelajaran Means Ends Analysis (MEA) terhadap Apresiasi Matematika dan Literasi Matematika Peserta Didik Kelas VII SMP Negeri 6 Denpasar Tahun Pelajaran 2017/2018: The Effect of Means Ends Analysis (MEA) Model to Mathematics Appreciaton and Mathematics Literacy of Seventh Grade Students in Smp Negeri 6 Denpasar Academic Year of 2017/2018 (FPMIPA IKIP PGRI Bali, 2019)
This study aimed to determine the effect of Means Ends Analysis (MEA) model to the interest and outcomes of mathematics learning of seventh grade students in SMP Negeri 6 Denpasar academic year of 2017/2018. The type of research was a quasi experiment and the design of research was non equivalent posttest-only control group design. The population were 9 classes of seventh grade students (364 students) in SMP Negeri 6 Denpasar which involved 2 classes as the sample taken by using multistage random sampling technique. The obtained data of this research used questionnaire and mathematics test score which furthermore analyzed by using MANOVA with SPSS 22.0 for Windows. Based on the obtained hypothesis test results: 1) there was an effect of Means Ends Analysis (MEA) model to the mathematics appreciation of seventh grade students in SMP Negeri 6 Denpasar academic of year 2017/2018, with the value 0,000 < 0,05, 2) there was an effect of Means Ends Analysis (MEA) modelto the mathematics literacy of seventh grade students in SMP Negeri 6 Denpasar academic year of 2017/2018, with the value 0,000< 0,05, and 3) there was an effect of Means Ends Analysis (MEA) modelto themathematics appreciation and mathematics literacyof seventh grade students in SMP Negeri 6 Denpasar academic year of 2017/2018, with the value 0,000< 0,05.